Problematika Supervisi Klinis pada Lembaga Pendidikan Islam di Indonesia - Aidil Rahman; Khairul Fajri; Gusmaneli Gusmaneli (CV. Alim's Publishing, 2024)
The clinical supervision process in Islamic educational institutions in Indonesia faces a number of problems that need attention. This article investigates the challenges in implementing clinical supervision at the Islamic educational level, including limited resources, understanding the concept of supervision, and the integration of Islamic values ​​in supervision practice. Through a qualitative analysis approach, this article also explores potential solutions to increase the effectiveness of clinical supervision in the context of Islamic educational institutions, with the aim of enriching student learning experiences and strengthening the integrity of Islamic values ​​in clinical education.